Problems of the theory of invariants and Lie algebras applied in the qualitative theory of differential systems - Mihail Popa (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
In this work there were formulated 18 problems from the theory of invariant processes, Lie algebras, commutative graded algebras, generating functions and Hilbert series, orbit theory and Lyapunov stability theory that are important to be solved. There was substantiated the necessity of using the solutions of these problems in the qualitative theory of differential systems.